Family, Identity, and the American Dream: Service Providers' Perspectives on Families' Experiences With Foreclosure. Issue 1 (January 2018) - Collins, Cyleste C.; Anthony, Elizabeth; Taylor, Debbie; Rothstein, David
This article reports the findings from in-depth qualitative interviews with 18 service providers who worked with families facing foreclosure. The interviews' purpose was to better understand a broad range of families' experiences and inductive coding focused on quotes that reflected the meaning of those experiences. The analysis extracted three main themes related to foreclosure representing threat: (a) foreclosure threatened children's education, (b) foreclosure threatened family memories, and (c) foreclosure threatened clients' sense of self and attaining the American Dream. Providers reported that families fought to keep their homes and hoped to buy again after foreclosure. The findings suggest that social work services could be beneficial in helping families navigate the emotional and financial impact of the foreclosure experience.